Efektivitas In-House Training Tentang HACCP Terhadap Tingkat Pengetahuan dan Sikap Penjamah Makanan - Ni Putu Pas Ryanti; Ni Putu Agustini; Badrut Tamam (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2026)
Food handler training is an important part of improving knowledge, skills, and quality of nutrition services in hospitals. This study aims to determine the effectiveness of in-house training on Hazard Analysis and Critical Control Point on the level of knowledge and attitude of food handlers in the Nutrition Installation of RSD Mangusada. The study used a pre-experimental design with a one group pretest-posttest approach, involving 35 food handlers. Data collection used a questionnaire and was analyzed using the Wilcoxon test at a 5% confidence level. The results showed that after training, all respondents (100%) showed an increase to the good knowledge category, and 62.9% showed a positive attitude. The level of effectiveness of training on knowledge was 0.82 in the high category in the first post-test and 0.52 in the medium category in the second post-test. The level of training effectiveness on attitudes is 0.65 and 0.51 in the medium category. The Wilcoxon test showed a significant difference (p <0.05) in the level of knowledge and attitudes before and after training. So it can be concluded that in-house training on HACCP is effective in improving the knowledge and attitudes of food handlers. Therefore, it is expected that the hospital will periodically conduct training and conduct monitoring and evaluation of the implementation of HACCP